Role of intraretinal and subretinal fluid on clinical and anatomical outcomes in patients with neovascular age‐related macular degeneration treated with bimonthly, treat‐and‐extend and as‐needed ranibizumab in the In‐Eye study. Issue 8 (15th March 2021) - Saenz‐de‐Viteri, Manuel; Recalde, Sergio; Fernandez‐Robredo, Patricia; López Gálvez, María Isabel; Arias Barquet, Lluís; Figueroa, Marta S.; García‐Arumí, José; García‐Layana, Alfredo; ,
Abstract: Purpose: To assess the effect of fluid status at baseline (BL) and at the end of the loading phase (LP) of three different ranibizumab regimens: treat‐and‐extend (T&E), fixed bimonthly (FBM) injections and pro re nata (PRN), in patients with neovascular age‐related macular degeneration (nAMD). Design: Post hoc analysis of the In‐Eye study (phase IV clinical trial). Methods: Patients were randomized 1:1:1 to the three study arms and were treated accordingly. The presence and type of fluid, intraretinal fluid (IRF) or subretinal fluid (SRF) and the anatomical and visual outcomes were analysed. Main outcome measures: Best‐corrected visual acuity (BCVA), the mean change from baseline BCVA (BL BCVA), and the proportion of eyes gaining more than 15 letters or losing more than five letters were analysed. Morphological characteristics including the subtype of choroidal neovascular membrane and the development of atrophy and fibrosis were also evaluated. Results: Patients with SRF at LP had better visual outcomes than patients with IRF. The persistence of SRF did not affect the mean change from BL BCVA among the three treatment regimens. However, in patients with IRF mean change from BL BCVA was significantly lower in the FBM group. The presence of IRF at BL and at the end of the loading phase was associated with the development of fibrosis at the end of the study; this result was contrary to that observed for patients with SRF. Conclusions: While SRF is compatible with good visual and anatomical outcomes, IRF leads to worse results in patients with nAMD; our results suggest that patients with IRF have better outcomes when individualized treatment regimens are used (PRN or T&E) in contrast with a FBM regimen.